Analisis Finansial Usaha Rumpon Pada Kelompok Usaha Bersama (Kub) Koral Minajaya Di Kota Sorong Papua Barat - Muhammad Ayusal Salam (Universitas Muhammadiyah Sorong, 2020)
Efforts to catch fish in large quantities require time and a large number of fishing gears as well as increasing fishing intensity. FADs is one method of fishing which aims to collect fish in a catchable area so that fishing can be done effecxtively and efficiently. This study aimed to analyze the FADs business run by Farmers and Fishermen Group Koral Minajaya Sorong City; to know the profit-sharing system and depositing dues or fees on group cash. This research was done with descriptive method which is based on case studies. The research resuxlts showed that investment cost is Rp.159.575.000; fixed cost is Rp. 162.075.000; variable cost is xRp. 156.370.000; and total cost is Rp. 318.545.000. Â production value is Rp. 1.119.040; absolute profit is Rp. 800.495.000. benefit cost ratio average is 3,51; break even point average is Rp. 188.401.403; Â and average payback period is 0.2 years (2 month). Results of the analysis indicated that the business FADs on KUB Koral Minajaya Sorong City was very profitable. Revenue sharing system was 70% for KUB Koral Minajaya and 30% for the company Joint of FADs on each fishing operations